Language Style Used by James Corden in the Late Late Show (e-Journal of Linguistics, 2023)
Language is one of the important things to communicate with others.People use language to show their emotions. There are five differentlanguage styles, frozen style, formal style, consultative style, casualstyle, and intimate style, which people can use to interact with others.People with different social cultures, ages, statuses, and gender mightuse different language styles. This study investigates James Cordon’sdifferent language style while interviewing his guest stars, James LeeCurtis, Dwayne Johnson, and Ed Sheeran, on The Late Late Show. Thestudy results show that James Corden used three different languagestyles: formal, casual, and consultative. As Jamie is older than James,he prefers to use formal language during the show. However, whileinterviewing Dwayne and Ed Sheeran, who are younger than James, heused different language styles, casual and consultative. The results ofthe study indicate that the age of the addressee considers the languagestyle preference.